2013
DOI: 10.1002/hbm.22355
|View full text |Cite
|
Sign up to set email alerts
|

White matter microstructure correlates of mathematical giftedness and intelligence quotient

Abstract: Recent functional neuroimaging studies have shown differences in brain activation between mathematically gifted adolescents and controls. The aim of this study was to investigate the relationship between mathematical giftedness, intelligent quotient (IQ), and the microstructure of white matter tracts in a sample composed of math-gifted adolescents and aged-matched controls. Math-gifted subjects were selected through a national program based on detecting enhanced visuospatial abilities and creative thinking. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
88
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 153 publications
(103 citation statements)
references
References 74 publications
13
88
1
1
Order By: Relevance
“…In an early study of roughly 50 children, 5 to 18 years old, Schmithorst et al (2005) found positive associations between white matter microstructure (i.e., DTI metrics) and intelligence, irrespective of age and sex. A more recent study of 36 children and adolescents 11 to 15 years of age also showed a positive association between white matter microstructure and intelligence (Navas-Sanchez et al, 2014). These studies show IQ to be linked to white matter microstructure in multiple regions, including frontal, parietal and occipital lobes, and the corpus callosum.…”
Section: Introductionmentioning
confidence: 73%
See 4 more Smart Citations
“…In an early study of roughly 50 children, 5 to 18 years old, Schmithorst et al (2005) found positive associations between white matter microstructure (i.e., DTI metrics) and intelligence, irrespective of age and sex. A more recent study of 36 children and adolescents 11 to 15 years of age also showed a positive association between white matter microstructure and intelligence (Navas-Sanchez et al, 2014). These studies show IQ to be linked to white matter microstructure in multiple regions, including frontal, parietal and occipital lobes, and the corpus callosum.…”
Section: Introductionmentioning
confidence: 73%
“…Previous work in children has demonstrated associations between white matter microstructure and IQ (Navas-Sanchez et al, 2014;Schmithorst et al, 2005). Schmithorst et al (2005) used a voxel-based approach to show positive associations between IQ and FA in multiple regions, particularly association bundles connecting frontal, parietal and occipital lobes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations